Prediction of grain supply and demand structural balance in China based on grey models. Issue 2 (17th July 2020) - Yang, Weiming; Li, Bingjun
Abstract : Purpose: The purpose of this paper is to comprehensively and accurately analyze the supply and demand structural balance of grain in the context of China's agricultural supply-side reform. By subdividing and forecasting the supply and demand, it is beneficial for targeted production in the case of clear demand and supply trends of main grain varieties. Design/methodology/approach: This paper forecasted and analyzed the demand of main grain varieties by the grey interval forecast, and based on the grey incidence analysis of more influence factors, forecasted the grain production with GM (1, N ) model. Findings: The results show that the demand and yield will keep sustainable growth in the next three years, while there is still a big gap between the supply and demand of the main grain varieties in China and the soybean's production is far behind the growing demand. Practical implications: This paper can make full use of the information to provide the evidence for government to formulate policies and put forward some correlative suggestions for growers. Originality/value: In this paper, the grey model technology is applied to the structural reform of grain supply side, and different models are used to predict the structural balance of supply and demand of different kinds of grain. The study of grain supply and demand structural balance in China is vital to ensure grain security in the context of agricultural supply-side reform.